Kajian Pengelolaan Pesisir berbasis Tipologi di Kabupaten Tanah Laut - Kiky Permana Setiawan (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
The coastal area of Tanah Laut Regency has two different coastal sides, namely the west and south coasts with different typologies on both coasts in terms of physical conditions and community activities. The purpose of this research is to know the typology in the West and South coastal areas of Tanah Laut Regency and the Coastal Management Concept based on coastal typology. The stages of data collection in this study consisted of secondary and primary data. Secondary data uses data from government agencies, studies, and regional planning documents, including data, geology, slope, topography, and satellite imagery for landforms. Based on the results of the analysis, there are 3 types of coastal typology groups, namely Marine Deposition Coast, Sub Aerial Deposition Coast, and Volcanic Coast. Coastal management strategies for the typology of the Sub Aerial Deposition Coast type such as planting mangroves, adaptation of vertical houses and coastal buildings. Meanwhile, the typology of the Volcanic Coast and Marine Deposition Coast is in the form of hard/protective buildings, coastal buildings, seawalls, and groins.